The effect of special exercises using a random visual device to develop the response speed of goalkeepers in futsal - Jameel, Ismaeel (Journal of Physical Education, 2025)
The objective of the research was to develop the response speed of futsal goalkeepers through the use of a random optical device due to the importance of the goalkeepers’ response speed in blocking the ball. The lack of response speed in blocking the ball is a problem, in addition to the lack of training of goalkeepers with advanced devices. The experimental method was used by designing the control and experimental groups in a manner that suited the nature of the study problem. The study sample was deliberately selected from some teams of the colleges of the University of Baghdad, numbering 16 futsal goalkeepers, 8 in the experimental group, and 8 in the control group. After conducting the exercises, analyzing, and discussing the results, the researcher concluded that statistically significant differences were found in the post-tests in favor of the experimental group. Through this, the researcher reached some conclusions and recommendations, the most important of which is that the use of the random optical device develops the response speed of futsal goalkeepers. Additionally, the effect of repeated exercises had a positive impact on the performance results.